Methodological strategy for the formation of information competencies with the use of ICTs - Guerra, Daniel José Olazabal; Velazco, Aylin Estrada (Advanced Notes in Information Science, 2024)
Competencies are currently defined and classified according to their trend. Among the competencies classified as basic-generic is the competence of information and knowledge management. In Cuba, informational competencies are trained in the postgraduate stage through information literacy programs; however, they should be trained during general or university education in order to provide society with a competent professional. With the objective of designing a methodological strategy for the formation of informational competencies with the use of information and communication technology (ICT), a quasi-experiment was developed in the Faculty of Health Technology of the University of Medical Sciences of Havana during the 2022 academic year. The methodological strategy was modeled and implemented in two independent samples. When the evaluation was carried out, it was obtained that 50% of the total sample reached the evaluation of good, while 36.8% was evaluated as excellent. The strategy was validated by experts with a high rating, while the validation of the students according to the satisfaction survey showed that 100% considered that the use of ICTs in the process of information competencies training had a positive influence, 91.6% considered that they acquired the competencies, and 100% expressed satisfaction with the use of ICTs during the development of the course. It is concluded that the methodological strategy for the formation of informational competencies with the use of ICT is valid for future generalization.